2019
DOI: 10.1115/1.4045259
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Assembly of Arrays of Lithographically Defined WS2 and MoS2 Monolayer Features Directly From Multilayer Sources Into Van Der Waals Heterostructures

Abstract: One of the major challenges in the van der Waals (vdW) integration of two-dimensional (2D) materials is achieving high-yield and high-throughput assembly of predefined sequences of monolayers into heterostructure arrays. Mechanical exfoliation has recently been studied as a promising technique to transfer monolayers from a multilayer source synthesized by other techniques, allowing the deposition of a wide variety of 2D materials without exposing the target substrate to harsh synthesis conditions. Although a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Moreover, the gold film evaporated on bP could have functioned as a clamping agent, adding/holding the biaxial compressive strain in bP. It is reported in our earlier work that metal evaporation on 2D materials results in the biaxial compressive strain due to the thermal expansion mismatch between the metal and material 56,57 . During photoconductor fabrication, except the 5s of g-line exposure, visible light exposure of bP was minimized to prevent photooxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the gold film evaporated on bP could have functioned as a clamping agent, adding/holding the biaxial compressive strain in bP. It is reported in our earlier work that metal evaporation on 2D materials results in the biaxial compressive strain due to the thermal expansion mismatch between the metal and material 56,57 . During photoconductor fabrication, except the 5s of g-line exposure, visible light exposure of bP was minimized to prevent photooxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Gold-mediated exfoliation has quickly attracted attention and has been utilized in the fabrication of flexible gas sensors, 4 lithography patterning for transistor applications, 5 and construction of large-area van der Waals (vdW) heterostructures. 6 , 7 …”
mentioning
confidence: 99%
“… 8 It was suggested that the MoS 2 –Au interaction is of vdW rather than covalent nature, and that when the Au is removed, the optical and electronic properties of monolayer MoS 2 match those of the semiconducting 1H phase, exfoliated directly onto insulating substrates. 2 , 3 , 5 , 6 This signifies that the metallicity of MoS 2 endowed by the Au 3 , 9 can be reversed after its transfer onto another substrate, significantly increasing the scope of this method to optoelectronics, photovoltaics, and photocatalysis. Despite these efforts, little is known about the nature of the interaction between MoS 2 and Au, its dependence on the number of MoS 2 layers, and specific effects brought about in MoS 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Flakes produced via this method have already been used in multiple applications including gas sensing, [13] photodetection, [14,15] and heterostructure arrays. [16,17] It has been claimed that the stronger Au/2D TMD interfacial interaction or binding energy (BE) of the top layer overcomes the weaker interlayer van der Waals (VdW) forces between the top layers and subsequent layers in TMD materials, thereby leaving behind largearea ML flakes. [9,12,18] The origin of stronger Au/2D TMDs is due to the well-known affinity of Au towards chalcogen atoms and is well studied in self-assembling monolayers (SAM) formation.…”
mentioning
confidence: 99%